Anti-discrimination law on the grounds of religion within the Italian legal system: Substantive and procedural aspects - Cettina Di Salvo (Anali Pravnog Fakulteta u Beogradu)
The author illustrates the normative framework of protection against religious discrimination in Italian legal system, scattered over several different pieces of legislation. The analysis is devoted to the substantive and procedural rules on the principle of equal treatment irrespective of religion. The analysis shows that the law guarantees every aspect of freedom of personal convictions in religious matter and protects not only people who belong to traditional organized religions, but all people who have held religious beliefs or practices. Italian law prohibits discrimination in regard to religion, not just in employment, but also in other areas. Consequently, the scope is wider than the EU Non-discrimination Directive 2000/78/EC, which only covers discrimination in employment, occupation and working conditions. The rules for the procedure before the court, designed to ensure the protection for persons who have been subject to discrimination are then examined. The author focuses in particular on the provisions regarding the legal standing, the burden of proof, and the remedies, which are crucially important for the effective implementation of the principle of equality.